The blink reflex test does not show abnormalities in a large group of patients with chronic migraine - Joseph Bruno Bidin Brooks; Yara Dadalti Fragoso (Arquivos de Neuro-Psiquiatria)
The blink reflex – a simple, non-invasive and inexpensive test – may be indicative of lesions or dysfunctions of the brainstem, and particularly assesses the trigeminal-facial arch. Results from alterations of the blink reflex in patients with headaches have provided controversial data. Method Registration of the waves R1 and R2 (ipsilateral to the stimulus) and R2c (contralateral to the stimulus) by electroneuromyography. Results A large number of controls (n=160) and patients with chronic migraine (n=160) were studied. No significant differences were observed between the two groups. Conclusion It is possible that this relatively simple and primitive reflex is not affected unless there is significant damage to the brainstem.